ダイ32ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク 1991 - 阿部, 豊雄; アベ, トヨオ; 岩本, 美代喜; イワモト, ミヨキ; 祐川, 淑孝; スケガワ, ヨシタカ; 稲吉, 浩; イナヨシ, ヒロシ; 青野, 正道; アオノ, マサミチ; Abe, Toyoo; Iwamoto, Miyoki; et al. (1994)
P(論文) この報告は第32次南極地域観測隊気象部門が, 1991年2月1日から1992年1月31日まで昭和基地において行った気象観測の結果, 1990年12月26日から1991年12月1日までのあすか観測拠点における気象観測の結果ならびに, 1990年11月から12月に行った「しらせ」船上でのオゾン観測結果をまとめたものである。観測方法, 設備, 結果の取扱い等は, 昭和基地及びあすか観測拠点とも第31次観測隊とほぼ同じである。なお, 昭和基地では, 紫外線B領域の観測を始めるなど地上放射観測の充実を図った。あすか観測拠点では, 南極気候変動研究計画の一環として気水圏研究部門が計画した, オメガゾンデによる高層気象観測を16回実施した。越冬期間中特記される気象現象としては, 次のものがあげられる。1) 昭和基地ではブリザードの襲来が34回あり, あすか観測拠点におけるブリザード日数は82日間あった。2) 昭和基地における年間の日照時間の合計値は観測開始以来最も少ない1684.9時間であった。3) 3年連続でオゾンホールを観測し, 日別値では9月30日のオゾン全量が159m atm-cmと観測開始以来2番目に低い値を記録した。4) 5月23日, 昭和基地付近でハイドローリックジャンプによる雪煙の渦塔が観測された。 This paper describes the results of meteorological observations carried out by the Meteorological Observation Team of the 32nd Japanese Antarctic Research Expedition (JARE-32) from 1 February 1991 to 31 January 1992 at Syowa Station, from 26 December 1990 to 1 December 1991 at Asuka Station and ozone observations from November to December 1990 on board the icebreaker SHIRASE. The observations, instruments and statistics at Syowa and Asuka Stations were the same as those of the JARE-31 observation team. In addition, at Syowa Station, ultraviolet-B radiation and other radiation observations were added for the Baseline Surface Radiation Network. At Asuka Station, aerological observations with 16 Omegasonde flights were carried out for the Antarctic Climate Research Program of the Meteorology and Glaciology group. The principal characteristics in the period of JARE-32 are as follows : 1) Blizzards at Syowa Station were encountered thirty-four times; the number of days of bizzards at Asuka Station was eighty-two. 2) At Syowa Station, the annual total sunshine duration was 1684.9 hours, which was the minimum record for the total period of observations. 3) The Antarctic ozone hole was observed for three successive years; the lowest value of daily total ozone amount was 159m atm-cm on 30 September, which was the second lowest value in the historical record. 4) On 23 May, a tower of snow smoke caused by hydraulic jump of katabatic wind was observed near Syowa ...